Pengembangan Video Animasi Sebagai Media Pembelajaran pada Capaian Sanggul Ukel Tekuk di SMKN 1 Sooko Mojokerto - Avril Lailia Fitri; M.A. Hanny Ferry Fernanda; Mutimmatul Faidah; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2024)
Obstacles that occur during the learning process can impact learning outcomes. Therefore, choosing the right media can facilitate and motivate students in learning. The selection of animation video-based media can boost students' enthusiasm for learning because its varied displays can capture students' attention. The purpose of this study is to investigate the feasibility of animation video-based learning media, how animation video media affects students' learning outcomes, and how students respond to the use of this media. This research uses a quantitative approach, with the research subjects being 31 students from class XI TKKR. Data were collected through observation, learning outcome tests, and questionnaires. The results are as follows: The quality of the feasibility of the animation video-based learning media received an average score of 92%, categorized as "very good." The psychomotor learning outcomes (practical) of the class XI TKKR students averaged 83.8, with 100% mastery, compared to the average KKTP score obtained from previous lessons using PowerPoint media and demonstrations, which scored 79. Students' responses received a score of 88%, categorized as "very good." Based on the research results, the development of animation video media for the topic of "ukel tekuk" hair bun is considered feasible for application in the learning process.